Nebuchadnezzar II. 604-592 B.C. - Muhammad, Hayat I. (1983)
?ay?h ’Ibr?h?m Mu?ammad; Nabūḫaḏnaṣṣar al-ṯānī 604-592 q.M.; Ba?dad 1983. al-?umh?riyyah al-’Ir?qiyyah. Wiz?rat al-taq?fah wal-’i’l?m. al-??’assasah al-‘?mmah lil-’???r wal-tur??; in Arabic. 140: English Abstract. M.A. College of Arts. University of Baghd